Selective harmonic elimination pulse width modulation based hybrid multilevel inverter topology with reduced components - Wasiq M.; Memon M.A.; Shrivastava P.; Mekhilef S.; Seyedmahmoudian M.; Stojcevski A.; Horan B. (John Wiley and Sons Inc, 2023)
Electric inverters; Harmonic analysis; Pulse width modulation; Simulink; Voltage control; Component count; Generation units; Hybrid multilevel inverter; Multilevel inverter topology; Output voltages; Pulsewidth modulations (PWM); Reduced switch; Selective harmonic elimination; Single phasis; Switch counts; Topology